2005
DOI: 10.1104/pp.105.060764
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Markers to Determine the Extent and Variability of Leaf Senescence in Arabidopsis. A Metabolic Profiling Approach

Abstract: Comparison of the extent of leaf senescence depending on the genetic background of different recombinant inbred lines (RILs) of Arabidopsis (Arabidopsis thaliana) is described. Five RILs of the Bay-0 3 Shahdara population showing differential leaf senescence phenotypes (from early senescing to late senescing) were selected to determine metabolic markers to discriminate Arabidopsis lines on the basis of senescence-dependent changes in metabolism. The proportion of g-aminobutyric acid, leucine, isoleucine, aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
181
2
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(206 citation statements)
references
References 42 publications
20
181
2
2
Order By: Relevance
“…In higher plants and green algae, photosynthetic carbon fixation is also reduced in response to nitrogen deprivation, and excess carbon is generally stored in molecular pools that contain little or no nitrogen. In higher plants, this is usually in the form of starch (Diaz et al, 2005;Wingler et al, 2006), and Peng et al (2007) described increased transcript levels of two genes involved in starch biosynthesis in Arabidopsis (Arabidopsis thaliana) under nitrogen starvation. In the fresh water green alga Chlamydomonas reinhardtii, on the other hand, excess carbon is reportedly directed to fatty acid biosynthesis (Wang et al, 2009;Moellering and Benning, 2010), and Miller et al (2010) found increased expression of genes involved in lipid biosynthesis in C. reinhardtii when nitrogen was not available.…”
Section: Interspecies Comparisonmentioning
confidence: 99%
“…In higher plants and green algae, photosynthetic carbon fixation is also reduced in response to nitrogen deprivation, and excess carbon is generally stored in molecular pools that contain little or no nitrogen. In higher plants, this is usually in the form of starch (Diaz et al, 2005;Wingler et al, 2006), and Peng et al (2007) described increased transcript levels of two genes involved in starch biosynthesis in Arabidopsis (Arabidopsis thaliana) under nitrogen starvation. In the fresh water green alga Chlamydomonas reinhardtii, on the other hand, excess carbon is reportedly directed to fatty acid biosynthesis (Wang et al, 2009;Moellering and Benning, 2010), and Miller et al (2010) found increased expression of genes involved in lipid biosynthesis in C. reinhardtii when nitrogen was not available.…”
Section: Interspecies Comparisonmentioning
confidence: 99%
“…Therefore, in order to consider the evidence of specific roles for metabolites in senescence, a more precise analysis of metabolite levels in different tissues and cell types during the process of senescence is required. Although, to date, a number of targeted metabolite profiles, particularly those focused on lipids as seed storage compounds (Yang and Ohlrogge, 2009;Seltmann et al, 2010) and sugars, amino acids, and nutrient ions (Masclaux et al, 2000;Quirino et al, 2001;Stessman et al, 2002;Diaz et al, 2005;Masclaux-Daubresse et al, 2005, 2007Pourtau et al, 2006;Wingler et al, 2006Wingler et al, , 2012, have been generated from maturing and senescing tissues, a broad overview of metabolic changes during senescence, including the interactions between various metabolic pathways, is still lacking. Therefore, we performed a metabolomics study to obtain comprehensive metabolite profiles, including primary and secondary metabolites and lipids, over the course of developmental senescence in rosette leaves before and after bolting and siliques of Arabidopsis in order to investigate the metabolic response and spatiotemporal distribution of metabolites during senescence at the whole-plant level and within single leaves.…”
mentioning
confidence: 99%
“…This allowed us to capture metabolite changes during the sink-source transition within a single leaf and to identify differences in metabolic patterns between presenescent and senescent tissues. This provides a spatiotemporal standard catalog of metabolites with which experiments affecting developmental processes, such as nutrient deficiency-induced senescence (Diaz et al, 2005;Watanabe et al, 2010;Obata and Fernie, 2012) or others, can be compared as well as marker metabolites for distinct senescence stages. The results are discussed in the context of current models of the metabolic shifts underlying developmental senescence.…”
mentioning
confidence: 99%
“…Another trait which has been found to interact with cold acclimation is leaf senescence (Masclaux-Daubresse et al 2007). During low-temperature exposure plants accumulate sugars (Cook et al 2004), an event that has been found to coincide with the onset of senescence in Arabidopsis and tobacco (Masclaux et al 2000;Diaz et al 2005). Cold acclimation in many woody plants is initially induced by short photoperiod and low, non-freezing temperatures.…”
Section: Communicated By S Aitkenmentioning
confidence: 99%